2022
DOI: 10.1039/d2ra03650a
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a non-enzymatic electrochemical sensor based on graphitic carbon nitride nanosheets for sensitive detection of procalcitonin

Abstract: A simple and ultra-sensitive electrochemical biosensor based on graphitic carbon nitride nanosheets (g-C3N4 NS) was developed for the detection of PCT. This sensor presented excellent sensing performance and demonstrates potential for clinical application.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…For the g-C 3 N 4 , they appeared layered, rippled and resembled waves of crumpled silk veil, illustrating the nanosheets structure (Figure 1A,D). Our previous research identified that this special nanosheet structure could provide more active binding sites [35]. For the NiCoP/g-C 3 N 4 nanocomposites, there were several small nanoparticles displayed on the g-C 3 N 4 surface, implying that NiCoP was successfully loaded onto the g-C 3 N 4 surface (Figure 1B,E).…”
Section: The Morphology and Structural Informationmentioning
confidence: 87%
See 1 more Smart Citation
“…For the g-C 3 N 4 , they appeared layered, rippled and resembled waves of crumpled silk veil, illustrating the nanosheets structure (Figure 1A,D). Our previous research identified that this special nanosheet structure could provide more active binding sites [35]. For the NiCoP/g-C 3 N 4 nanocomposites, there were several small nanoparticles displayed on the g-C 3 N 4 surface, implying that NiCoP was successfully loaded onto the g-C 3 N 4 surface (Figure 1B,E).…”
Section: The Morphology and Structural Informationmentioning
confidence: 87%
“…XRD was used to distinguish the phases and the structures of bare g-C 3 N 4 and NiCoP loading. As shown in Figure 2, the lattice planes of triazine units (100) (13.1 • ) and the lattice planes of interlayer stacking of aromatic segments (002) (27.8 • ) were detected, indicating the bare g-C 3 N 4 was successfully synthesized [35,39]. For the NiCoP/g-C 3 N 4 samples, beside the strongest diffraction peaks of g-C 3 N 4 , several weak peaks appeared at 41 • , 44.95 • and 47.97 • , which correspond to the (111), ( 201) and (210) lattice planes of NiCoP, respectively [40,41] (JCPDS No.…”
Section: The Morphology and Structural Informationmentioning
confidence: 93%
“…The probe peptide (PP) is connected to the electrode surface through π-π stacking between g-C 3 N 4 NS and phenylalanine at the end of the peptide, providing efficient electrochemical solutions for ultrasensitive detection of PCT (Fig. 5 C) [ 56 ]. An ultrasensitive sandwich electrochemical method was employed for PCT testing.…”
Section: Chemiluminescent Immunoassay For Pct Detectionmentioning
confidence: 99%
“…Copyright 2020 American Chemical Society. (C) Schematic diagram of preparation of PCT electrochemical biosensor [ 56 ]. Copyright 2022 Royal Society of Chemistry.…”
Section: Chemiluminescent Immunoassay For Pct Detectionmentioning
confidence: 99%
“…It is composed of 116 amino acids and is produced by parafollicular cells (C cells) of the thyroid and by the neuroendocrine cells of the lung and the intestine. 10,11 Early differentiation between septic and non-septic arthritis and the possible decision for therapy remains a difficult task for the physician because clinical signs and traditional markers of infection are of limited value. 12,13 Arthrocentesis with synovial gram stain and culture is considered as gold standard, however, the sensitivity of the gram stain is only 50-75% and culture is not available immediately.…”
Section: Introductionmentioning
confidence: 99%